2020
DOI: 10.1038/s41401-019-0330-9
|View full text |Cite
|
Sign up to set email alerts
|

Fecal microbiota transplantation improves metabolism and gut microbiome composition in db/db mice

Abstract: Fecal microbiota transplantation (FMT) has become an effective strategy to treat metabolic diseases, including type 2 diabetes mellitus (T2DM). We previously reported that the intestinal microbiome had significant difference between individuals with normal glucose tolerance and T2DM in Chinese Kazak ethnic group. In this study, we investigated the effects of transplanted fecal bacteria from Kazaks with normal glucose tolerance (KNGT) in db/db mice. The mice were treated with 0.2 mL of fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 32 publications
3
41
0
1
Order By: Relevance
“…S2B). However, in our model and as published by many authors (38)(39)(40), fasting glucose was slightly lower after FMT in comparison to sham FMT, but significantly lower when compared to WD-fed, antibiotics-treated, S-gavaged mice that did not receive DS (two-way ANOVA showed a main effect of FMT gavage # P = 0.0042; Sidak post hoc, *P = 0.04) (SI Appendix, Fig. S2C).…”
supporting
confidence: 78%
“…S2B). However, in our model and as published by many authors (38)(39)(40), fasting glucose was slightly lower after FMT in comparison to sham FMT, but significantly lower when compared to WD-fed, antibiotics-treated, S-gavaged mice that did not receive DS (two-way ANOVA showed a main effect of FMT gavage # P = 0.0042; Sidak post hoc, *P = 0.04) (SI Appendix, Fig. S2C).…”
supporting
confidence: 78%
“…In rodent models, insulin sensitivity significantly improved after transferring microbiota in MyD88 deficient NOD mice ( 109 ). Similar studies where human microbiota from healthy Chinese subjects are transplanted into diabetic db/db mice remarkably lowers fasting blood glucose concentrations ( 110 ). Likewise, transplantation of fecal samples of patients treated with metformin into germ-free mice improves glucose tolerance ( 111 ).…”
Section: Therapeutic Potential Of Gut Microbiota For T2dmentioning
confidence: 79%
“…121 Some parenteral diseases are also being explored, such as autism, 122 obesity, 123 and type 2 diabetes. 124 Vrieze et al 125 performed FMT treatment on patients with metabolic syndrome, and the result indicated that patients receiving gut flora from leptin donor displayed improved insulin sensitivity and increased butyrate production. This finding was validated in another RCT, suggesting that FMT might be a potential treatment strategy for metabolism-related diseases.…”
Section: Tang Et Al (2013) 133mentioning
confidence: 99%